ӘДЕБИЯТ САБАҚЛАРЫНДА ИНТЕРАКТИВ МЕТОДЛАРДЫ ПАЙДАЛАНЫЎ - Юсупов, И.К. (FAN va JAMIYAT, 2021)
The article describes the methods of using interactive technologies in teaching Karakalpak literature and methodologi- cal issues of their teaching for classes 5-11.